Análise comparativa da infiltração marginal apical de três cimentos endodônticos através de um processo de diafanização - Villela, Alexandre Mascarenhas (2007)
The success of endodontic treatment is directly related to the correct implementation of all its phases, from diagnosis to your proservation. The shutter system root canal is no exception to this rule and deserves special attention because it is the phase that ends the treatment itself. The filling material should seal the entire root canal system, space formerly occupied by the root pulp, providing a hermetic sealing and three-dimensional. Over the years various materials have been tested, but now the use of gutta-percha (solid material) associated with a sealer (plastic material) is almost unanimous. The gutta-percha should be the main material of the shutter and must occupy the greatest possible proportion of the light of the root canal system. However, sealers have shown to influence, directly, the success of endodontic treatment. Numerous studies have been and are still being carried out in an attempt to develop a cement covering all the physicochemical and biological characteristics of a filling material. This study aimed at comparing the capacity of apical sealing of cement: Sealer 26®, Acroseal® and EndoREZ®. All experiments were performed in Endodontics Research Laboratory of the Dental School of the State University of Rio de Janeiro. It was concluded that none of the tested cements was able to prevent the apical infiltration in all tested teeth. After statistical analysis, the Sealer 26® cement and cement Acroseal® no statistically significant differences, contrary to cement EndoREZ® which showed a much lower and statistically significant